2009
DOI: 10.1136/jme.2008.025940
|View full text |Cite
|
Sign up to set email alerts
|

Do research ethics committees identify process errors in applications for ethical approval?

Abstract: We analysed Research Ethics Committee (REC) letters. We found that RECs frequently identify process errors in applications from researchers that are not deemed "favourable" at first review. Errors include procedural violations (identified in 74% of all applications), missing information (68%), slip-ups (44%) and discrepancies (25%). Important questions arise about why the level of error identified by RECs is so high, and about how errors of different types should be handled.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 17 publications
4
30
0
Order By: Relevance
“…They reported that 6.0% of the researchers believed that the FICF was not necessary, 44.0% of the research subjects were not informed on the existence of ethical committees and 12.0% of the researchers believed that the quality of research monitoring could be improved. Angell et al 10 reported a high rate of errors identified by the REC, which corroborates the importance of submitting a project to the assessment of a REC before initiating the research.…”
Section: Discussionsupporting
confidence: 49%
“…They reported that 6.0% of the researchers believed that the FICF was not necessary, 44.0% of the research subjects were not informed on the existence of ethical committees and 12.0% of the researchers believed that the quality of research monitoring could be improved. Angell et al 10 reported a high rate of errors identified by the REC, which corroborates the importance of submitting a project to the assessment of a REC before initiating the research.…”
Section: Discussionsupporting
confidence: 49%
“…The process errors were: procedural violation, missing information, slip-ups and discrepancies -all four were devised by Angell and Dixon-Woods; [7] and an additional four are my categories, namely: informed consent, confidentiality, study sample, and legal.…”
Section: Methodsmentioning
confidence: 99%
“…[2] Briefly they comprise: • procedural violations [7] -failure to comply with application procedures • missing information [7] -inadequate information to understand an application • slip-ups [7] -minor errors • discrepancies [7] -inconsistencies • informed consent [2] -inadequate or poorly written consent documents ARTICLE • confidentiality [2] -inadequate protection of participants • study sample [2] -inappropriate choice, missing permission from relevant authorities • legal [2] -contrary to SA law, potential incrimination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to spend time getting this right as many committee members begin by reading this part, and most feedback involves changes to the information sheet 7. NRES provide substantial guidance on writing these, and I would suggest that you use their sample templates for guidance, although these should be modified to suit the specifics of your project vi…”
Section: Application Processmentioning
confidence: 99%